Kelayakan Usaha Tempe Di Kecamatan Weru, Kabupaten Cirebon - Lestari, Dhea Nandaputri; Dyah, Pujastuti S. (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Weru District is one of the centers of home industry in Cirebon Regency. The products produced include tempeh, tofu, gapit, kerupuk mlarat, and others. Tempeh products in Weru District are not only distributed in the local market but also distributed to other areas. In 2020, there has been a decrease in the amount and an increase in the price of imported soybeans. This makes it difficult for tempeh producers to obtain the raw material for making tempeh. Therefore, producers reduce the use of soybeans which have an impact on reducing the amount of production. However, the set selling price doesn’t increase so that producers don’t lose their consumers even though their profit decrease. This study aims to determine the cost, income, and profit, as well as to determine feasibility of tempeh business in Weru District, Cirebon Regency. Data was collected by interview method using a questionnaire to 40 tempeh entrepreneurs. The research data is divided into 3 business scales based on the use of raw materials. The research data were analyzed using the R/C, capital productivity, and labor productivity. This study obtained the results of the R/C value on a small business scale of 1,09, R/C on a medium scale of 1,08, R/C on a large scale of 1,18, capital productivity on a small business scale of 105,69%, capital productivity on a medium scale of 108,06%, capital productivity on a large scale of 136,50%, labor productivity on a small business scale of Rp. 303.877/HKO, labor productivity on a medium scale of 289.365/HKO, and labor productivity on a large scale of 494.817/HKO. This means that the tempeh business in Weru District, Cirebon Regency is feasible because it shows positive results.